The Bradycardic Agent Ivabradine Acts as an Atypical Inhibitor of Voltage-Gated Sodium Channels - Hackl, Benjamin; Lukacs, Peter; Ebner, Janine; Pesti, Krisztina; Haechl, Nicholas; Földi, Mátyás C; Lilliu, Elena; Schicker, Klaus; Kubista, Helmut; Stary-Weinzinger, Anna; Hilber, Karlheinz; Mike, Arpad; et al. (Frontiers in Pharmacology, 2022)
Background and purpose Ivabradine is clinically administered to lower the heart rate, proposedly by inhibiting hyperpolarization-activated cyclic nucleotide-gated cation channels in the sino-atrial node. Recent evidence suggests voltage-gated sodium channels (VGSC) to be inhibited within the same concentration range. VGSC are expressed within the sino-atrial node and throughout the conduction system of the heart. A block of these channels thus likely contributes to the established and newly raised clinical indications of ivabradine. We therefore investigated the pharmacological action of ivabradine on VGSCs in sufficient detail in order to gain a better understanding of the pro- and anti-arrhythmic effects associated with the administration of this drug. Experimental Approach Ivabradine was tested on VGSCs in native cardiomyocytes isolated from mouse ventricles and from the His-Purkinje system and on human Nav1.5 in a heterologous expression system. We investigated the mechanism of channel inhibition by determining its voltage-, frequency-, state-, and temperature- dependence, complemented by a molecular drug docking to the recent Nav1.5 cryoEM structure. Automatic patch clamp experiments were used to investigate ivabradine mediated changes in Nav1.5 inactivation parameters and inhibition of different VGSC isoforms. Key results Ivabradine inhibited VGSCs in a voltage- and frequency-dependent manner, but did not alter voltage-dependence of activation and fast inactivation, nor recovery from fast inactivation. Besides cardiac Nav1.5, neuronal (Nav1.2) and skeletal muscle (Nav1.4) VGSC isoforms were inhibited by ivabradine. Sodium currents in native cardiomyocytes isolated from the ventricles and the His-Purkinje system were inhibited with similar potency. Molecular drug docking revealed an interaction of ivabradine with the classical local anaesthetic binding site. Conclusion and Implications Ivabradine acts as an atypical inhibitor of VGSCs. Inhibition of VGSCs likely contributes to the heart rate lowering effect of ivabradine, in particular at higher stimulation frequencies and at depolarised membrane potentials, and to the observed slowing of intra-cardiac conduction. Inhibition of VGSCs in native cardiomyocytes and across channel isoform provides a basis for the anti-arrhythmic potential as observed upon administration of ivabradine.